Taxonomic status of the partial calvaria a.l. 333-45 from the Late Pliocene of Hadar, Ethiopia - Ferguson, Walter W (Bernard Price Institute for Palaeontological Research, 1992)
The taxonomic status of a partial calvaria, A.L. 333-45, from the late Pliocene of Hadar, in Ethiopia, classified as a hominid and paratype of "Australopithcus afarensis" Johanson, White and Coppens 1978 is reassessed. Its total morphological pattern and adaptive affinities agree with the Pongidae, and do not exhibit a single unequivocal hominid character. The evidence in fact suggests that A.L. 333-45 represents a relatively generalized ape, the only pongid calvaria known from the late Pliocene of Africa: and may be the first skull found of Praeanthropus africanus (Weinert), 1950. Moreover, this indicates that the fossils assigned to "Australopithecus afarensis'' do not represent a single taxon: and that the reconstruction of the skull of a male "A. afarensis" seems to be a composite of pongid and hominid fossils.
Keywords: australopithecus; afarensis; chimaera; pongidae